An Analysis of the Factors Influencing Non-Performing Loans at Perumda BPR Garut - Rahmanisa, Riska; Dewi Ungkari, Marti; Kartiko, Erik (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This research was organized under the title: "Analysis of the factors that influence non-performing loans at Perumda BPR Garut". Reviewing the importance of controlling the non-performing loans (NPL) level in banks, This study aims to obtain data and information regarding the factors that influence non-performing loans at Perumda BPR Garut. The object of this research is Perumda BPR Garut and what is studied is related to the factors that influence non-performing loans at Perumda BPR Garut. n this research, the authors employed multiple linear regression techniques to analyze the data with questionnaires as technique to collect the data. The outcomes of the research lead to the conclusion that the factors affecting non-performing loans at Perumda BPR Garut are external factors consisting of the dimensions of the debtor's character, the debtor's business conditions and the debtor's managerial ability. So that banks need to provide guidance to customers who fall into the category of non-performing loans.